Algorithm efficiency in a crude context - Walker, John; Naidu, Laila; Smith, Daniel (InTech, 2004)
With oil prices approaching $50 per barrel and natural gas prices near $6 per million British thermal units, acting on any opportunity to improve the efficiency of existing process equipment to reduce energy costs is essential. For hug fuel boilers, improved control of the combustion process can happen by reducing the level of excess oxygen, which directly translates into improved boiler efficiency. Here, Walker et al discuss the operating issues involved.